The enunciation of student knowledge and the cultural curriculum of Physical Education - Santos Júnior, Flávio Nunes dos (2023)
In the midst of Modernity, a single way of living was raised as legitimate and true, representing the effects of the civilizing course. This dynamic led to the consummation of countless lives, experiences were, knowledge exterminated and certain ways of being erased. Institutional education and science served this purpose of a colonial, patriarchal and capitalist character. Modern pedagogy is heir to this legacy based on the idea of ​​progress through reason and scientific development with the promise of the formation of a supposed autonomous, conscious and, above all, free subject. The cultural curriculum of Physical Education faces such intentions by taking a stand in defense of differences. This research examines whether and as a teacher who claims to put the proposal into action, values ​​students' knowledge about thematic body practice. To this end, it sought support in the qualitative form of investigation through participant observation and group conversations. The materials produced when submitted to the confrontation with the decolonial thought of the Latin American group Modernidade / Colonialidade, the epistemologies of the South of Boaventura Sousa Santos and the post-colonialism of Homi Bhabha, indicate that the students perceive the environment conducive to listening, which motivates them to expose their gestures and knowledge. This finding allows us to infer that when putting culturally oriented Physical Education into action, the teacher is guided by the ethical-political principle that favors the enunciation of students' knowledge.